Problem: Shortage of Pastors—Solution: Religious Robots? - Tretter, Max (Social Robots in Social Institutions. Proceedings of Robophilosophy 2022, 2023)
Many Christian churches around the world are struggling with a shortage of pastors—leading to long vacancies in some parishes and posing great challenges for pastors who have to fill in these gaps. This raises the question of whether pastoral shortage could be solved technologically by providing each vacant parish with social robots that could take over the religious tasks and replace lacking human workforce. Based on a comprehensive literature review on social robots in religious contexts, I provide an overview of robots that already perform religious acts around the world and consider the discussions that arise about them. From these considerations, I conclude that social robots cannot and should not (yet) replace human pastors. However, they can assist human pastors and thereby address and mitigate the negative effects of the pastor shortage in some ways.
Keywords: Robots; Theology; Robotics; Pastoral Shortage; AI